EFFECTIVE METHODS OF REGENERATION OF USED MOTOR OILS - Boyturayev, Sarvar; JURAEV , TULKINJON; ISMAILOV , OYBEK (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, the increasing demand for oil produced as a result of oil refining and the damage it causes to the environment as a result of its use, as well as the analysis of the global growth trend of the need for lubricants are presented. Taking into account the increasing need for lubricants, we conducted research on the processing of used oils. . In our experiments, studies were conducted using chloride, nitrate, sulfate, vinegar, trichloracetic acids for oil processing by acid adsorbent method. The viscosity, viscosity index, and cloud point of the oils obtained as a result of the research were compared with the physical properties of new and used oils. The results of our experiments show that it is possible to obtain good results in the processing of oils using the acid adsorption method.